KEGIATAN PERJALANAN SUCI DAN KEMAH BHAKTI (PSKB) DALAM MEMBENTUK SIKAP SOSIAL - Ade Khairun Zanah; Annisa Lestari Harahap; Elza Syaskia Hasibuan (Journal of Community Devation, 2024)
This research aims to find out about camping. This research uses descriptive qualitative research, documentation methods. Research result . Implementation of the Holy Journey and Camp of Service (PSKB) is a spatial training and field training activity that maximizes social and spiritual values. Supporting factors for implementing PSKB activities in forming social and spiritual attitudes include: Internal factors: The presence of enthusiasm, sincerity, and comply with the existing rules in PSKB activities. External factors: Moral support from agencies, motivation provided by retired students and previous seniors who have taken part in PSKB and all participants encouraging each other. Factors inhibiting the implementation of PSKB activities in forming social and spiritual attitudes include: Internal factors: Lack of compliance with regulations, tiredness, bad words (talking dirty). External factors: Unfavorable weather and difficult permitting for the implementation location.